Junior Travel & Tours / Mohd. Hakimi Jamil ... [et al.] - Jamil, Mohd. Hakimi; Sedik, Suzliana; Shamsudin, Norazwanataty; Jaafar, Mohd. Fazlien; Ahmad, Fazellette; Rusly, Nadiatul Liza (Faculty of Hotel and Tourism Management, 2003)
This company is established under the Companies Act 1965 on the 15th November 2003 and is a wholly owned Bumiputra Company. This company is also registered with several Government Ministries as a travel agent. Under the Tourism Act 1992, this company has obtained the travel agency license no: KKKL / PL 1502. The main activity of this business is specializing in tour operators. We are specialized in educational tour, which provides the services for primary school students. Itinerary, shuttle bus, food & beverages and places of interests are the components that fully arranged by our company. As we know, there are a lot of schools in Shah Alam, means higher opportunities to get potential customers. As a different type of travel agent we will take the initiative to provide the services for educational tour.